Design, fabrication and testing of a power operated paddy dibbler - JAYARAJAN R; Er. Jippu Jacob (Guide) (Tavanur 1996 Kelappaji College of Agricultural Engineering and Technology)
two row power operated paddy dibbler. designed KCAET, Tavanur. two seed boxes, plungers
Design, fabrication and testing of a power operated paddy dibbler